المقارنة بين العملات المشفرة والنقود الشرعية نظراً إلى رعاية العرف: دراسة فقهية تحليلية: A Comparative Analysis of Cryptocurrencies and Shariah-Compliant Money with Reference to Custom (‘Urf): An Analytical Jurisprudential Study - Wahidullah , Azaam; Bt MEGat Laksana, Nan Noorhidayu; Zakaria, Muhammad Sabri (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2025)
ملخص البحث تهدف هذه الدراسة إلى بحث الحكم الشرعي للعملات المشفرة من خلال تأصيلها على مفهوم النقود عند الفقهاء؛ فقد قصر جمهور فقهاء المالكية والشافعية والحنابلة مفهوم النقود على ما له قيمة ذاتية (طبيعية)، في حين وسّعه بعض فقهاء الحنفية، ورواية عن الإمام مالك، وقول منسوب إلى الإمام أحمد، ليشمل ما يثبت له النقدية بالعرف. وتُوظف الدراسة مناهج الاستقراء والتحليل والمقارنة، حيث تستعرض النصوص الفقهية التقليدية إلى جانب الوظائف الأساسية للنقود وتطورها التاريخي، وصولًا إلى ظهور العملات الافتراضية مثل "البيتكوين"، مما أثار تساؤلاً حول مدى اعتبار هذه العملات نقوداً معترفاً بها بناءً على العرف السائد. وقد تباينت آراء العلماء بين القائلين بالجواز، والمانعين، والمترددين، إلا أن الدراسة ترجّح القول بالجواز المشروط بضوابط شرعية وقانونية واضحة. وبما أن مرجعية النقود في حقيقتها تعود إلى العرف، فإن كل ما يُقبل عرفاً وسيطاً للتبادل ومقياساً للقيمة يُعدّ نقداً. وعلى الرغم من المخاوف المتعلقة بغياب الرقابة الحكومية وإمكانية الاستغلال في جرائم كغسل الأموال، فإن الدراسة ترى أنه متى ما وُضعت لها أطر تنظيمية معتبرة، فإن التعامل بالعملات المشفرة يعد جائزاً، إذ تمثل هذه العملات تطوراً رقمياً للأدوات النقدية، وبناء عليه توصي الدراسة بضرورة وضع تنظيمات شرعية وقانونية واضحة تكفل سلامة المعاملات وتحفظ مصالح جميع الأطراف المعينة. ABSTRACT This study seeks to examine the legal ruling on cryptocurrencies by grounding them within the classical Islamic conception of money. While the majority of Maliki, Shafi’i, and Hanbali jurists restricted the definition of money to that which possesses intrinsic (natural) value, some Hanafi scholars, along with a narration from Imam Malik and an opinion attributed to Imam Ahmad, extended the definition to include that which is established by customary usage. Employing inductive, analytical, and comparative methodologies, the study explores traditional jurisprudential texts alongside the core functions of money and its historical development, culminating in the emergence of virtual currencies such as Bitcoin. This has raised the question of whether such currencies can be deemed valid money through prevailing custom. Scholarly opinions diverge between permissibility, prohibition, and hesitation; however, the study supports the view that conditional permissibility is most appropriate—provided that such currencies are regulated by clear Shariah and legal standards. Since money derives its legitimacy from custom, anything widely accepted as a medium of exchange and a measure of value qualifies as money. Despite concerns over the lack of governmental oversight and potential misuse, such as in money laundering, the study argues that with proper regulatory frameworks, the use of cryptocurrencies is permissible, as they represent a digital evolution of monetary instruments. Accordingly, the study recommends the establishment of clear legal and Shariah-based regulations to safeguard transaction integrity and protect the interests of all parties involved.